TINGKAT PENDAPATAN DAN KESEJAHTERAAN KELUARGA PEKERJA HARIAN PERKEBUNAN KELAPA SAWIT (Studi Kasus di PT Prima Mitrajaya Mandiri Kecamatan Kota Bangun) (Income Level and Family Welfare of Daily Worker of Oil Palm Plantation (Case Study in PT Prima Mitrajaya Mandiri Kota Bangun Subdistrict)) - SEPTIAN WAHYU SAPUTRA; NDAN IMANG (Universitas Mulawarman (University of Mulawarman), 2020)
The establishment of an oil palm company provides a change in the family welfare of daily workers in its plantation. The purpose of this study were to determine the income and welfare of oil palm family of daily worker of oil palm plantation. This research was conducted from August to September 2019 in PT Prima Mitrajaya Mandiri (PT PMM), Kota Bangun Subdistrict. The number of respondents was 52 workers. Data were analyzed by descriptive method. The results of this reserach showed the average income of daily worker in section of fertilization as much as IDR22,179,196.00 year-1, weed control as much as IDR23,907,101.00 year-1, and harvesting as much as IDR38,477,611.00 year-1. The average of family income of daily worker from working in oil palm company and from non oil palm (farm, off-farm, and no-farm) in section of fertilization, weed control, and harvesting were IDR33,625,350.00 year-1; IDR30,678,529.00 year-1; and IDR40,061,611.00 year-1, respectively. Based on the average per capita income per year, the daily worker family of oil palm plantation of PT PMM was categorized welfare.